Report from the select committee of the House of Lords appointed to enquire into the price at which foreign grain may be shipped in foreign ports . the quantity of such grain; and the price at which such grain can be imported into this country; and to report to the House: with the minutes of evidence, appendix and index.; (N.pl., 1827)
PAMPHLET VOLUME.